Impacts of the English Language Acquisition on Language Learners’ Culture and Identity: The Iranian EFL Contexts - Rahimi Pordanjani, Sadegh (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Researchers and sociolinguists report that culture and language are inextricably intertwined by highlighting “language is culture and culture is language”, they believe that language is a crucial tool for individuals to maintain their culture and identity. Due to several functions of the English language in different sectors such as education, communication, and business, the number of language learners willing to learn this language is growing. As a result, numerous concerns have been raised in the field of sociolinguistics towards the acquisition of this language. Sociolinguists have been worried about some major effects of the English language acquisition on language learners’ mother-tongue, culture, and identity. They report that English as a major language influences many minor languages and changes the language learners' culture and identity negatively. This article aims to review various literature in order to identify some of the impacts of the English language learning which can have influential roles on the Iranian EFL learners’ culture and identity in language centers and universities.